THE QUALITY OF LIFE OF ADOLESCENTS LIVING IN A CLOSED ADMINISTRATIVE TERRITORIAL UNIT - S.F. Sosnina; D.K. Volosnikov ("Paediatrician" Publishers LLC, 2010)
The article illustrates results from a study of the quality of life of adolescents aged 15-17 living in a closed administrative territorial unit (town of Ozersk) using the questionnaire PedsQL 4.0. It describes the questionnaire survey of 309 children and their parents with the comparison group made up of 298 families from a nearby town. On the whole, no differences were identified in the overall assessment of quality of life indicators in both groups, which indicates there is no impact of a specific town on this category of population. Key words: adolescents, quality of life, closed administrative territorial unit.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):10-13)